Romance in the Recent Past: Our Beloved Summer and First Love in the Ecology of Netflix Global Programming - Vivien Nara (Global Storytelling)
This article offers a reflection on two recent romance series offered by Netflix: Our Beloved Summer (2021) from Korea and First Love (2022) from Japan. Both series were seen as successes for their local industries, and a review of their production histories as well as their place within a broader Netflix programming ecology highlights the strategies Netflix is taking with its increased investment in the drama production industries of both nations. Importantly, both series also share a temporality in their romance storytelling, one that moves between a youthful, recent past and a lackluster, adult present. Though the texts are not necessarily adjacently marked in the Netflix interface itself, both series present key similarities that hint at a winning narrative formula. Drawing on key scholarly literature on popular romance and modernity, I argue that while the temporality of “romance in the recent past” might not necessarily be marked as a working microgenre in the Netflix algorithm, it certainly presents as a transnationally translatable storytelling mode that narrativizes, entertains, and consoles audiences coming from similar experiences of modernity.